The endocannabinoid-CB2 receptor axis protects the ischemic heart at the early stage of cardiomyopathy - Duerr, Georg D.; Heinemann, Jan C.; Suchan, Georg; Kolobara, Elvis; Wenzel, Daniela; Geisen, Caroline; Matthey, Michaela; Passe-Tietjen, Kristine; Mahmud, Walid; Ghanem, Alexander; Tiemann, Klaus; Alferink, Judith; et al. (Basic Research in Cardiology, 2014)
Ischemic heart disease is associated with inflammation, interstitial fibrosis and ventricular dysfunction prior to the development of heart failure. Endocannabinoids and the cannabinoid receptor CB2 have been claimed to be involved, but their potential role in cardioprotection is not well understood. We therefore explored the role of the cannabinoid receptor CB2 during the initial phase of ischemic cardiomyopathy development prior to the onset of ventricular dysfunction or infarction. Wild type and CB2-deficient mice underwent daily brief, repetitive ischemia and reperfusion (I/R) episodes leading to ischemic cardiomyopathy. The relevance of the endocannabinoid-CB2 receptor axis was underscored by the finding that CB2 was upregulated in ischemic wild type cardiomyocytes and that anandamide level was transiently increased during I/R. CB2-deficient mice showed an increased rate of apoptosis, irreversible loss of cardiomyocytes and persistent left ventricular dysfunction 60 days after the injury, whereas wild type mice presented neither morphological nor functional defects. These defects were due to lack of cardiomyocyte protection mechanisms, as CB2-deficient hearts were in contrast to controls unable to induce switch in myosin heavy chain isoforms, antioxidative enzymes and chemokine CCL2 during repetitive I/R. In addition, a prolonged inflammatory response and adverse myocardial remodeling were found in CB2-deficient hearts because of postponed activation of the M2a macrophage subpopulation. Therefore, the endocannabinoid-CB2 receptor axis plays a key role in cardioprotection during the initial phase of ischemic cardiomyopathy development. © 2014 Springer-Verlag.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Cardiomyopathy; Cardioprotection; Endocannabinoids; Macrophages; Myocardial remodeling